Soybean microbiome composition and the impact of host plant resistance - Tran, Dung T.; Mitchum, Melissa G.; Zhang, Shuzhen; Wallace, Jason G.; Li, Zenglu (Frontiers in Plant Science, 2024)
Microbial communities play an important role in the growth and development of plants, including plant immunity and the decomposition of complex substances to absorbable nutrients. Hence, utilizing beneficial microbes becomes a promising strategy for optimization of plant growth. The objective of this research was to explore the root bacterial profile across different soybean genotypes and the change in microbial community under soybean cyst nematode (SCN) infection in greenhouse condition using 16S rRNA sequencing. Soybean genotypes with soybean cyst nematode (SCN) susceptible and resistant phenotypes were grown under field and greenhouse conditions. Bulked soil, rhizosphere, and root samples were collected from each replicate. Sequencing of the bacterial 16S gene indicated that the bacterial profile of soybean root and soil samples partially overlapped but also contained different communities. Bacterial phyla Proteobacteria, Actinobacteria and Bacteroidetes dominate the soybean root-enriched microbiota. The structure of bacteria was significantly affected by sample year (field) or time point (greenhouse). In addition, the host genotype had a small but significant effect on the diversity of the root microbiome under SCN pressure in the greenhouse test. These differences may potentially represent beneficial bacteria or secondary effects related to SCN resistance.